Characterization of stratum corneum structure in reconstructed epidermis by X-ray diffraction. - J A Bouwstra; G S Gooris; A Weerheim; J Kempenaar; M Ponec (Journal of Lipid Research, 1995)
The intercellular lipid regions in the stratum corneum (SC), the outermost layer of the skin, form the major barrier for diffusion of substances through the skin. The barrier function of in vitro reconstructed epidermis is still impaired. With respect to further optimization of the model, it is necessary to characterize its stratum corneum lipid structure. In this study, small and wide angle X-ray diffraction were used to characterize the lipid organization in stratum corneum isolated from 14-day-old reconstructed epidermis. The measurements were carried out at room temperature, and subsequently as a function of temperature between 25 degrees C and 109 degrees C, followed by measurements after cooling to room temperature. The results of the X-ray diffraction measurements revealed the following in reconstructed epidermis. 1) The lamellar ordering of stratum corneum lipids was much lower than that observed in native stratum corneum. 2) Crystalline anhydrous cholesterol was present. 3) Orthorhombic packing was present, but the corresponding reflections were very weak. The orthorhombic packing disappeared between 30 degrees C and 45 degrees C. 4) A hexagonal packing was present and disappeared between 60 degrees C and 75 degrees C. 5) Soft keratin is present. 6) A higher extent of lamellar ordering could be achieved by heating to 109 degrees C and cooling down to room temperature. Analysis of SC lipids revealed the presence of high amounts of triglycerides, the level of which could be decreased by lowering the glucose content. However, modulation of culture medium composition did not significantly affect lipid lamellae structures or hydrocarbon chain packing.